OPTIMISATION OF THE PHOTOVOLTAIC GRID CONNECTED SYSTEM USING FUZZY LOGIC CONTROL - TKOUTI, N.; MOUSSI, A. (Courrier du Savoir; Vol. 6 (2005): Courrier du Savoir)
This paper presents a maximum power point tracker (MPPT) using fuzzy logic for a PV grid connected system. Since the PV array characteristic is hardly nonlinear, conventional control technics could be inefficient for an optimal use of these systems. Knowing that PV systems are still very expensive, therefore a fuzzy logic controller is proposed to ensure the transfer of the maximam power to the utility grid system. This method has proved its effeciency and robustness inspite of climatic conditions variations.